2015
DOI: 10.1016/j.jcrs.2014.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative endophthalmitis from 1990 to 2009 using povidone–iodine but no intracameral antibiotics at a single academic institution

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 29 publications
1
34
2
1
Order By: Relevance
“…Since the top centers only account for 3.1% of the hospitals in China [statistics reported by the National Bureau of statistics of China (http://data.stats.gov.cn)], the results of the current survey are more representative of the present medical treatment level in most Chinese hospitals. In developed countries, the incidence of postoperative endophthalmitis ranges from 0.012 to 0.076%3456789, which is far less than in our study. Recently, the European Society of Cataract & Refractive Surgeons (ESCRS) recommended the intracameral injection of 1 mg of cefuroxime at the close of cataract surgery10.…”
Section: Discussioncontrasting
confidence: 73%
“…Since the top centers only account for 3.1% of the hospitals in China [statistics reported by the National Bureau of statistics of China (http://data.stats.gov.cn)], the results of the current survey are more representative of the present medical treatment level in most Chinese hospitals. In developed countries, the incidence of postoperative endophthalmitis ranges from 0.012 to 0.076%3456789, which is far less than in our study. Recently, the European Society of Cataract & Refractive Surgeons (ESCRS) recommended the intracameral injection of 1 mg of cefuroxime at the close of cataract surgery10.…”
Section: Discussioncontrasting
confidence: 73%
“…The reported incidence of postoperative endophthalmitis after cataract surgery varies from 1 in 300 to 1 in 14,000 depending upon the geographic location and surgical techniques used [2, 3]. Besides sterile technique, other proven innovations that have decreased the incidence of endophthalmitis following cataract surgery include use of preoperative povidone/iodine cleansing solution and small incision phacoemulsification techniques [4, 5]. At the present time, there is no general consensus in regard to the effectiveness of topical antibiotics for reducing the rates of endophthalmitis after cataract surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…No intracameral antibiotics were used. 36 These rates are comparable to the group that received intracameral cefuroxime in the ESCRS study. 13 The above two studies thus found reduced incidence of endophthalmitis with increasing volumes and concentrations of povidone iodine.…”
Section: Peri-operative Measuresmentioning
confidence: 69%